Earthquake predictions and scientific forecast: dangers and opportunities for a technical and anthropological perspective - Tapia-Hernández, Edgar; Reddy, Elizabeth A.; Oros-Aviles, Laura Josabeth (Earth Sciences Research Journal, 2019)
Supporting earthquake risk management with clear seismic communication may necessitate encounters with various popular misapprehensions regarding earthquake prediction. Drawing on technical data as well as insights from anthropology and economics, this paper addresses common and scientifically-unsupported ideas about earthquake prediction, as well as the state of science-based studies regarding statistical forecasting and physical precursors. The authors reflect on documented social and economic effects of unsubstantiated earthquake predictions, and argue that these may be dangerous but may also present certain opportunities for outreach and education in formal and informal settings. This paper is written in light of the importance that the United Nations Office for Disaster Risk Reduction has placed on coordination and communication within and among diverse organizations and agencies as well as by recent popularity of so-called earthquake prediction in Mexico.